Trends, reasons and prospects of de-dollarization - Yuefen Li (South Centre, 2023)
The 1944 "Bretton Woods Agreement" gave birth to the new international financial system marked by the centrality of the US dollar which is a crucial pillar of the global power of the United States. Over the past eight decades, the asymmetry of the shrinking US economic weight in the world economy and growing dominant role of the dollar has become more and more glaring. The disadvantages of overreliance on the dollar have been keenly felt, especially by developing countries. The recent moves to weaponize the dollar and the payment clearance system have triggered another wave of reassessment by national states and enterprises of the role of the dollar and led to the hitherto most broad-based de-dollarization process covering from Southeast Asia to Latin America and the Middle East. De-dollarization has been incrementally taking place in different forms and led by BRICS and some commodity exporting countries. However, there are many challenges to meaningful de-dollarization. Overall, de-dollarization efforts, despite important progress, have been limited and partial. There has been progress in reducing overreliance on the dollar through foreign exchange reserve diversification and trade invoicing as evidenced by the decline in the dollar's share of allocated foreign exchange reserves and the increase of trade invoiced and transacted in currencies other than the dollar. However, on aspects requiring the deep financial market and wide network such as foreign exchange transactions, issuance of debt and payment clearance, the dollar's share has not suffered a decline. To reform the international financial system, the BRICS in particular should continue to take the lead in furthering the de-dollarization efforts.
Keywords: 300; BRICS; Currency; De-dollarization; Debt; Digital Currency; Dollarization; Foreign Exchange; Foreign Reserves; Geoeconomics; Global Economy; International Financial Architecture; International Trade; Reform of the International Financial System; SWIFT